2020
DOI: 10.1186/s12903-020-01233-0
|View full text |Cite
|
Sign up to set email alerts
|

A new method for assessment of nickel-titanium endodontic instrument surface roughness using field emission scanning electronic microscope

Abstract: Background: To introduce a new method for measurement of surface roughness of the endodontic instrument, before and after instrumentation, using the Field Emission Scanning Electronic Microscope (FE-SEM) combined with the ImageJ software. Methods: Twenty J-shape resin blocks were divided into two groups, ten blocks of each group. Simulated root canal inside the resin block was 16 mm length, 60 0 angle of curvature, and radius of 4.5 mm. Ten WaveOne Gold Primary and 10 Reciproc Blue R25 instruments were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
3
13
0
1
Order By: Relevance
“…To analyze the SR of NiTi files, a variety of techniques have been used [30][31][32][33][34][35]. Atomic force microscopy (AFM) and SEM are the most commonly used methods to evaluate the surface characteristics of endodontic files.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the SR of NiTi files, a variety of techniques have been used [30][31][32][33][34][35]. Atomic force microscopy (AFM) and SEM are the most commonly used methods to evaluate the surface characteristics of endodontic files.…”
Section: Discussionmentioning
confidence: 99%
“…SEM has the disadvantage that only qualitative evaluations can be obtained, as the two-dimensional images created by SEM cannot be processed for quantitative surface data [38]. However, a number of researchers have shown that data obtained via field-emission SEM (FE-SEM) is reliable and accurate, and, therefore, SEM and ImageJ software were used to measure SR values and recreate three-dimensional images [34,[39][40][41]. In the present study, the SR of three thermally treated NiTi instruments (i.e., TN, PTG, and ETP) is evaluated using SEM aided by ImageJ software after multiple autoclaving sterilization cycles.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve microstructure of the working surface of Ni-Ti instruments and improve mechanical properties, flexibility, fatigue resistance, i.e. cutting efficiency, manufacturers have used various techniques in recent years (ionic application, plasma immersion, titanium oxide coating, thermal nitriding, thermal treatments and cryogenic treatments, electropolishing) [3,26,28,30].…”
Section: Discussionmentioning
confidence: 99%
“…U svrhu poboljšanja mikrostrukture radne površine Ni-Ti instrumenata i poboljšavanja mehaničkih osobina, fleksibilnosti, otpornosti na zamor, odnosno sečivne efikasnosti, proizvođači poslednjih godina primenjuju različite tehnike (jonska implementacija, plazma imerzija, formiranje premaza titanijum-oksida, termalna nitridacija, termalni tretmani i kriogeni tretmani, elektropoliranje) [3,26,28,30].…”
Section: Diskusijaunclassified
“…The shaping procedure of root canals has significant effect on success of endodontic treatment. [1][2][3] icroorganisms, dentin chips, pulp tissue or irrigation solution may be extruded into the periapical tissues during the biomechanical preparation. 4 .The apical extrusion phenomenon may cause unwanted postoperative complications such as pain, periapical inflammation, delay of periapical healing, and edema.…”
Section: Introductionmentioning
confidence: 99%